Analysis of Voluntary Disclosure Program, Tax Socialization, and Tax Collection Actions on Tax Fairness with Tax Compliance as a Moderating Variable - Ayu Puspita Sari; Annathasia P. Erasashanti (CV. Megantara Abdi Nusa, 2026)
This study aims to analyze the effects of the Voluntary Disclosure Program (VDP), Tax Socialization, and Tax Collection Actions on Tax Fairness, with Tax Compliance as a moderating variable. The study was conducted on taxpayers registered at the South Jakarta Primary Tax Service Office (KPP Pratama Jakarta Selatan) using a quantitative approach. Primary data were collected through questionnaires distributed to 161 respondents selected by simple random sampling. The analytical methods employed were multiple linear regression and Moderated Regression Analysis (MRA) using IBM SPSS 25 software. The results indicate that the Voluntary Disclosure Program has a significant negative effect on Tax Fairness, Tax Socialization has a significant negative effect on Tax Fairness, and Tax Collection Actions have a significant positive effect on Tax Fairness. Furthermore, Tax Compliance was proven to moderate the effects of all three independent variables on Tax Fairness strengthening the influence of the Voluntary Disclosure Program and Tax Socialization, while weakening the influence of Tax Collection Actions. These findings suggest that the level of taxpayer compliance plays a crucial role in shaping the perception of Tax Fairness within the jurisdiction of KPP Pratama Jakarta Selatan.